2011
DOI: 10.1016/j.chembiol.2010.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ligands for a Purine Riboswitch Discovered by RNA-Ligand Docking

Abstract: SummaryThe increasing number of RNA crystal structures enables a structure-based approach to the discovery of new RNA-binding ligands. To develop the poorly explored area of RNA-ligand docking, we have conducted a virtual screening exercise for a purine riboswitch to probe the strengths and weaknesses of RNA-ligand docking. Using a standard protein-ligand docking program with only minor modifications, four new ligands with binding affinities in the micromolar range were identified, including two compounds base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
136
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(137 citation statements)
references
References 61 publications
1
136
0
Order By: Relevance
“…Riboswitches appear capable of manipulating the expression of genes related to metabolite biosynthesis without direct interaction with proteins. Moreover, riboswitches have been suggested as potential drug targets (Blount and Breaker 2006;Blount et al 2007;Kim et al 2009;Lee et al 2009;Cressina et al 2011;Daldrop et al 2011;Deigan and Ferré-D'Amaré 2011;Maciagiewicz et al 2011) and for a number of potential engineering applications (Wieland and Hartig 2008;Link and Breaker 2009;Topp and Gallivan 2010), highlighting the importance of understanding mechanisms for specificity and recognition of riboswitches by small molecule ligands Haller et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Riboswitches appear capable of manipulating the expression of genes related to metabolite biosynthesis without direct interaction with proteins. Moreover, riboswitches have been suggested as potential drug targets (Blount and Breaker 2006;Blount et al 2007;Kim et al 2009;Lee et al 2009;Cressina et al 2011;Daldrop et al 2011;Deigan and Ferré-D'Amaré 2011;Maciagiewicz et al 2011) and for a number of potential engineering applications (Wieland and Hartig 2008;Link and Breaker 2009;Topp and Gallivan 2010), highlighting the importance of understanding mechanisms for specificity and recognition of riboswitches by small molecule ligands Haller et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many high-affinity riboswitch-binding purine and lysine analogs have been discovered (3,9), and in silico modeling efforts have expanded the arsenal of tool compounds (10). In some cases, biochemical and structural information about riboswitches and their cognate ligands is far more advanced than our knowledge of the underlying pathogen biology being targeted.…”
mentioning
confidence: 99%
“…We are only aware of five studies in which the suitability of RNA-ligand docking for virtual screening was assessed [56,58,65,71,75]. Encouragingly, it was demonstrated that virtual screening performs better than random selection using either ICM, GOLD, Ribodock, Autodock, DOCK 3.5 or DOCK 4.0 as docking engine [56,58,65,71,75].…”
Section: Performance Of Rna-ligand Dockingmentioning
confidence: 97%
“…Moitessier et al extended AutoDock to account for RNA flexibility and changes in the first hydration shell [59]. When using different versions of DOCK below version 6, the atom parameters were taken from the AMBER force field [78], however, the phosphate backbone was neutralized by adjusting the partial charges of the involved atoms [56,65]. DOCK 6 is an extension of DOCK 5 but was specifically optimized for RNA-ligand docking [68].…”
Section: Protein-ligand Docking Programs Applied To Rna-ligand Dockingmentioning
confidence: 99%